Trace elements in Spanish foods of animal origin. IV.- Birds and various (Revista Española de Fisiología, 1948)
This paper is the fourth of a series the object of which is the study of catalytic elements contained in Spanish food of anima! origin. Investigation of the oligoelements of said biological materials are realized by means of spectrochemical technique. The results of analysis of 29 samples are included, 23 of which correspond to different birds and 6 to other divers foodstuffs of animal origin such as honey and eggs.This being the fourth and last note referring to the composition of oligoelements in animal foodstuffs, some considerations on the total results are also included, as well as general conclusions deducted therefrom, which may prove interesting for a review of the total work.